Pemberdayaan Masyarakat Desa Padang Ratu, Kecamatan Sungkai Utara, Kabupaten Lampung Utara Melalui Pembuatan Gula Cair dari Singkong Sebagai Pemanis Alternatif - Setiawan, Rizkima Akbar; Priyana, Fahrur Riza; Khawarizmi, Muhammad Nur; Fikri, Muhammad; Awansah (FT Universitas Lampung, 2025)
The production of cassava liquid sugar using enzymatic hydrolysis technique is one of the innovations that aims to utilize the potential of local resources into high-value and useful products. This article attempts to provide an overview and explanation related to the work program for producing liquid sugar from cassava, including the process, stages, results, and benefits. This article was written using a qualitative approach with a descriptive-explanatory model. As a result, the community received new understanding and insights in terms of producing liquid sugar from cassava. This article is limited to the implementation of KKN Period 1 of 2025.